Distributed fault detection and isolation in second order networked systems in a cyber–physical environment. (August 2020) - Khan, Aadil Sarwar; Khan, Abdul Qayyum; Iqbal, Naeem; Sarwar, Muhammad; Mahmood, Atif; Shoaib, M. Asim
Abstract: Modern industrial processes and cyber–physical systems (CPS) are prone to anomalies both due to cyber and physical perturbations. Cyber disturbances or attacks being more hazardous may give birth to a series of multiple coordinated faults. In order to detect and isolate such faults, this paper proposes a novel distributed fault detection and isolation scheme for second-order networked systems. The system is assumed to be working in a cyber–physical environment where it is likely to face multiple simultaneous faults. Each node has access to measurements of states of its neighboring nodes. A distributed fault detection and isolation filter (DFDIF) is designed such that fault detection and fault isolation can be obtained in a single step. Using the proposed filter, each node can detect and isolate multiple simultaneous faults in its neighboring nodes. The detection and isolation of faults with a single filter at each node reduces the overall computational burden of distributed fault detection and isolation (DFDI) scheme. The proposed framework is tested for power network and robotic formations. Finally, a comparison with existing techniques is provided to prove the effectiveness of the proposed method. Highlights: A novel fault detection and isolation scheme is proposed with lesser computational burden. Detection and isolation of coordinated multiple simultaneous falts is achieved Uniform allocation of computational resources is assured